Festival Rules Anger School Steel bands - Joseph, Terry (Trinidad Express)
The Junior Steelband Music Festival may be in jeopardy, stemming from Pan Trinbago's alteration of one of the longstanding rules of the competition. The new rule no longer limits selection of the band's tune of choice to pieces written by Caribbean composers. The school bands are saying that the competition has lost its focus.
Keywords: Pan Trinbago (Organization); Steel bands (Music) -- Competitions -- Trinidad and Tobago; Junior Steelband Festival; Steel bands (Music) -- Administration -- Trinidad and Tobago